2017
DOI: 10.1016/j.jaip.2016.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Analysis of Peanut Flour Used in Oral Immunotherapy Clinical Trials

Abstract: Background Oral immunotherapy (OIT) is an investigational therapeutic approach for the treatment of food allergies. Characterization of the drug product used in oral immunotherapy trials for peanut allergy has not been reported. Objective To quantify relative amounts of the major peanut allergens and microbial load present in peanut flour used in OIT trials and assess whether these parameters change over a 12 month period. We also anticipate that this report will serve as a guide for investigators seeking to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…OIT and SLIT studies were IRB approved and study drug administered under INDs . OIT Trial #1 listed below was designed with the primary goal of assessing SU after several years on therapy, while OIT Trial #2 was focused on desensitization with a shorter treatment duration.…”
Section: Methodsmentioning
confidence: 99%
“…OIT and SLIT studies were IRB approved and study drug administered under INDs . OIT Trial #1 listed below was designed with the primary goal of assessing SU after several years on therapy, while OIT Trial #2 was focused on desensitization with a shorter treatment duration.…”
Section: Methodsmentioning
confidence: 99%
“…One study showed that peanut flour contains the major peanut allergens Ara h 1 and Ara h 2 in complete form and thus can be a viable product for peanut OIT with its low bacterial content and long shelf life. 36 In recent years, 2 types of T-cell epitope-based allergen peptides have been developed and assessed in RCTs: short T-cell epitope peptides (also named synthetic peptide immunoregulatory epitopes) and longer contiguous overlapping peptides (COPs). 37 Previous trials with cat, 38 HDM, 39 and grass 40 synthetic peptide immunoregulatory epitope immunotherapy were encouraging.…”
Section: Advances In Ait Routes and Preparationsmentioning
confidence: 99%
“…We selected light roasted peanut flour because it is a commonly used food ingredient and it can represent other heat-treated peanut products in terms of roasting degree. Furthermore, it is available as a well-characterized material and has been used in many peanut allergy studies because of its high lot-to-lot consistency [ 27 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%